Understanding the Te Whāriki approach : early years education in practice - Lee, Wendy. (Understanding the ... approach, 2013)
"Understanding the Te Whāriki Approach is a much-needed source of information for those wishing to extend and consolidate their understanding of the Te Whāriki approach, introducing the reader to an innovative bicultural curriculum developed for early childhood services in New Zealand. It will enable the reader to analyse the essential elements of this approach to early childhood and its relationship to quality early years practice. Providing students and practitioners with the relevant information about a key pedagogical influence on high quality early years practice in the United Kingdom, the book explores all areas of the curriculum, emphasising: - strong curriculum connections to families and the wider community; - a view of teaching and learning that focuses on responsive and reciprocal relationships with people, places and things; - a view of curriculum content as cross-disciplinary and multi-modal; - the aspirations for children to grow up as competent and confident learners and communicators, healthy in mind, body, and spirit, secure in their sense of belonging and in the knowledge that they make a valued contribution to society; - a bicultural framework in which indigenous voices have a central place. Written to support the work of all those in the field of early years education and childcare, this is a vital text for students, early years and childcare practitioners, teachers, early years professionals, children's centre professionals, lecturers, advisory teachers, head teachers and setting managers"--